Biomimetic Coating of Modified Titanium Surfaces with Hydroxyapatite Using Simulated Body Fluid - Mohsin Nazir; Ong Pei Ting; Tan See Yee; Saravanan Pushparajan; Dasan Swaminathan; Muralithran G. Kutty (Advances in Materials Science and Engineering)
This study investigated the viability of coating commercially pure titanium (CPTi) surfaces, modified via sandblasting and acid etching, with hydroxyapatite (HA)/tricalcium phosphate coatings using a simulated body fluid (SBF) solution. The samples were immersed in SBF from 3 to 7 days. The morphology and the chemistry of the HA/tricalcium phosphate coating were then analysed. Prior to immersion in SBF, the samples were sandblasted and acid etched to mimic the morphology and roughness of commercially available dental implants. The SBF aided in the formation of crystalline HA/tricalcium phosphate coatings on all the samples. The coatings were uniform and had roughness values higher than the underlying substrate. The highest roughness values for the coatings on the surfaces were obtained at 7 days of immersion in SBF with average Sa values of 2.9 ± 0.2 µm. The presence of HA/tricalcium phosphate on the surfaces was confirmed by the Scanning Electron Microscope (SEM), Energy Dispersive Spectrometer (EDS), the X-Ray Diffraction (XRD), and the Fourier Transform Infrared Spectrometer (FTIR) analysis. This study shows that it is possible to obtain an adequate and uniform hydroxyapatite coating on pure titanium substrates in a shorter period of time with characteristics that favour the ultimate goal of implants therapy, that is, osseointegration.